GENDER STRUGGLES BEHIND THE SCENES: REPRESENTATION AND ROLE OF FEMALE JOURNALISTS IN NEWS PRODUCTION - Effendi, Ahmad Yasser; Nasution, Deddy Parwis Jailani (Academic Solution Publisher, 2025)
The journalism profession in Indonesia is still dominated by men, both in terms of editorial leadership and division of labor in the field. This article discusses how female journalists construct their roles and face obstacles in the news production space, as well as how gender representation is reflected in everyday journalistic practices. Using a sociological approach and gender perspective, this article attempts to uncover the power relations, stereotypes, and negotiation strategies experienced by female journalists in navigating a masculine work environment. This study uses a qualitative method with in-depth interview techniques with female journalists from various mass media. The findings show that although women experience marginalization in editorial decision-making and field assignments, they still play an important role in encouraging a more inclusive perspective in the news. This study emphasizes the importance of structural awareness of gender equality in the media industry and the need for a more equitable transformation of journalistic work culture.